National Intelligence University's Role in Interagency Research Recommendations from the Intelligence Community - Johnston, Judith A. (RAND Corporation, 2013)
To help the Center for Strategic Intelligence Research (CSIR) of the National Intelligence University (NIU) better identify collaborative research opportunities, topics, and processes with Intelligence Community research entities, this study details the results of semistructured interviews conducted with a purposive sample of representatives to capture information about these research entities, their responsibilities, and their willingness to support interagency research with NIU.